Prinsip-Prinsip Ahl al-Sunnah wa al-Jama`ah: Pengenalan dan Terjemahan Melayu Wasiyyah Imam Abu Hanifah - Mamat, Mohd Anuar; Mohd Akib, Mohd Manawi; Husin, Basri (Afkar: Jurnal Akidah dan Pemikiran Islam, 2014)
Imam Abu Hanifah was one of the most prominent scholars and mujtahid in Islam. He had left some valuable works in the field of Islamic Theology (Aqidah) and Fiqh (jurisprudence) for his disciples. Among his works are his Wasiyyah that underline the principles of Ahl al-Sunnah wa al-Jama`ah. He reminded his disciples to stick with the Ahl al-Sunnah wa al-Jama`ah and not to obey the innovators (mubtadi`) or those who follow their desires (sahib hawa). Then, he constructed and formularized twelve principles of Ahl al-Sunnah wa al-Jama`ah as a guidance for the Muslim community. This Wasiyyah is indeed essential for the Malay community in present days in obtaining the accurate understanding of Ahl al-Sunnah wa al-Jama`ah, however it is not yet to be translated into Malay. Thus, this article will present a brief introduction on Abu Hanifah, the validity of the Wasiyyah that belongs to him, a brief review of the Wasiyyah contents and its Malay translation. Although this treatise is only a short explanation as written in the form of matan, its contents are valuable and suitable to serve as the basic principles of Ahl al-Sunnah wa al-Jama`ah in facing the present theological challenges.